Global expansion of Mycobacterium tuberculosis lineage 4 shaped by colonial migration and local adaptation - Brynildsrud, Ola B. (2021)
On the basis of population genomic and phylogeographic analyses of 1669 Mycobacterium tuberculosis lineage 4 (L4) genomes, we find that dispersal of L4 has been completely dominated by historical migrations out of Europe. We demonstrate an intimate temporal relationship between European colonial expansion into Africa and the Americas and the spread of L4 tuberculosis (TB). Markedly, in the age of antibiotics, mutations conferring antimicrobial resistance overwhelmingly emerged locally (at the level of nations), with minimal cross-border transmission of resistance. The latter finding was found to reflect the relatively recent emergence of these mutations, as a similar degree of local restriction was observed for susceptible variants emerging on comparable time scales. The restricted international transmission of drug-resistant TB suggests that containment efforts at the level of individual countries could be successful.